Analisis Perhitungan Harga Pokok Produksi Berdasarkan Metode Full Costing pada UMKM Dodonut di Kabupaten Karawang - Tiar Lina Situngkir; Anastasia Putri Sidiq Sidiq; Aiska Amini; Adhelia Purnama Alam; Annisa Hanan; Diah Marwati; Lulu Mamlukah (CV. Ulil Albab Corp, 2024)
All businesses must pay close attention to the calculation of the cost of production because in this day and age, MSMEs are increasingly competing to produce high-quality goods at competitive prices. Cost of Production is the overall cost incurred in converting raw materials into finished products and as a benchmark to compare whether the selling cost will be too high or too low. However, there are still many business owners who do not estimate the overall cost of production. This can lead to an inaccurate assessment of the company's profit or loss. In this study, we look at how the determination of the full cost of goods and the approach of the Micro, Small, and Medium Enterprises (MSMEs) Dodonut are used to determine the price of the goods produced. Business owners may be able to find a middle ground between MSME HPP and full costing technique HPP by calculating and comparing the two. The Full Costing method calculates production costs using raw materials, direct labor, and fixed and variable plant overhead costs. The majority of this research data comes from Dodonut MSME owners. Dodonut MSME interviews and records themselves are used to collect data. Production costs reached Rp 25,483,367 when the full cost approach was used, and Rp 18,784,024 when the MSME method was used. This study reports the findings from the overall cost calculation of the production cost strategy.